Moving Beyond Individual-Level Explanations: Exploring the Contextual Correlates of Mass Murder - Fridel, Emma E. (Criminal justice and behavior, 2022)
Due to the rarity of mass murder, scholars have focused almost exclusively on its individual-level risk factors, assuming that structural characteristics play a negligible role in the etiology of this infrequent but impactful crime. This study explores whether local structural factors influence the incidence rate of mass murder and its logical comparison group, homicide. Using information from a novel mass killing database as well as the Supplementary Homicide Reports (SHR), two-level count regression models examine the county- and state-level factors that predict the number of mass murder (N = 549) and homicide incidents (N = 274,399) in 3,143 U.S. counties from 2000 to 2018. Results indicate that mass murder is more likely to occur in disadvantaged and racially/ethnically heterogeneous areas, similar to homicide in general. Future research should examine both perpetrators and their environments instead of assuming that mass murders are exclusively driven by individual-level factors.